The challenges of digital work in Portugal - Rebelo, G.; Roxo, M. (La construcción del derecho del trabajo de las redes empresariales, 2019)
In May 2010 the European Commission adopted the Communication A Digital Agenda for Europe (COM (2010) 245 final), setting out a strategy for the digital economy by 2020, which was one of the seven flagship initiatives under the Europe 2020 Strategy, presents policies aimed at maximizing the benefits of the digital age for all sectors of society and the economy, especialy the creation of a digital single market as well as the improvement of ICT skills and application.